Impact of Research Methodology Training on Research Skill Development of Faculties - Hakuduwal, Kishor (Bagiswori Journal, 2019)
The study aims to analyze the perception of faculties on their research skill development through research methodology training conducted by Bagiswori College, a renowned community college in Bhaktapur district affiliated to Tribhuvan University. The training schedule, teaching pedagogy and learning environment are taken as independent variables and research skill development is taken as dependent variable. Data are collected through closed ended questionnaire. Five point Likert scale using strongly disagree, disagree, agree to some extent, agree, strongly agree was made to know the perception of participated faculties on research skill development through research methodology training. The study has used regression, mean score, t-test and F-test for the analysis of data. The study has found that the teaching pedagogy and the learning environment of research methodology training have significant impact on perceived faculties’ research skill development and training schedule of research methodology training has not significant impact on perceived faculties’ research skill development.